Using colloquial language in prose fiction texts: An exploratory study - Al-Alami, Suhair Eyad Jamal (Research Journal in Advanced Humanities, 2024)
Prose fiction texts have an aesthetic function, which seeks to create a sense of aesthetic appreciation through means of language style amongst other devices. Bearing this in mind, it is the author’s belief that using colloquial language in a prose fiction text may negatively impact language style of the text and acquisition of the foreign language. Motivated by this conviction, this study addresses two main questions. First, how does use of colloquial language impact language style of a prose fiction text? Second, how does use of colloquial language impact language acquisition in relation to foreign and second English learners? For data gathering purposes, the author of this paper created and distributed a questionnaire comprising ten items. Including three groups: English as a Foreign Language (EFL) students; EFL university instructors; and adult readers, the questionnaire was addressed to a total of one hundred and sixty-six subjects in Dubai. Moreover, the researcher conducted a semi-structured interview involving six subjects. According to the statistical results, most of the respondents and interviewees believed that including colloquial language in prose fiction texts would negatively impact language style of the text and acquisition of the foreign language.